Does Gearing Influence on Corporate Performance? Evidence from Kenya (International Journal of Management and Sustainability, 2019)
The objective of this paper was to determine the influence of gearing and corporate performance of non-financial firms listed on the NSE. The target population being 42 companies with 35 companies meeting the threshold for a balanced panel regression for the period 2008-2017. The study adopted longitudinal quantitative research design with random-effects GLS models. The corporate performance was assessed by ROCE and Q ratio while gearing was measured using leverage ratio. The findings reveal that the gearing is positively and statistically insignificant related with corporate performance of the listed non-financial firms at the NSE measured using ROCE and positively significantly related to Tobin’s Q. This paper commends the necessity to cultivate a worthy rapport with debt capital providers such as banking companies, and other financial institutions to benefit from easy acquisition of large sums of funds and enjoy the interest tax shields related to interest charged on debt finance.